Gayo Aceh Coffee Supply Chain Risk Dynamics Modeling: Covid-19 Pandemic, Inventory, Supply Chain Disruption, Profits - Dedi Kurniawan; Suharno Suharno; Dwi Rachmina (Jurnal Penelitian Pertanian Terapan, 2023)
The Covid-19 pandemic presents a significant risk for coffee players, especially for Gayo farmers in Central Aceh Regency. Including price risk, supply and demand risk, and supply chain risk. This study aims to study the dynamics of the supply chain in Gayo coffee caused by Covid-19 by measuring the supply level and profits of Gayo coffee actors. The type of data in this study used cross-section data. Data were collected for this study at a particular time. Sources of data in this study include primary data and secondary data. Sample selection was carried out by snowballing a sample of critical cooperatives/gathering traders with the following selection criteria: (i) farmers, collectors, and Gayo Arabica coffee cooperatives connected to the supply chain; (ii) Gayo Arabica coffee farmers, collectors, and cooperatives have experienced and experienced supply chain disruptions during the Covid-19 pandemic. The analysis used in this study uses a dynamic modeling system to simulate changes in inventory levels and profits caused by disruptions in production, supply, and sales). The results influence the level of supply and profits of coffee supply chain actors due to disruption from the COVID-19 pandemic. One of them is a decrease in earnings for coffee players and an increase in supply for sales actors (cooperatives). The increase in operational costs also affects the level of coffee supply chain actors.